2016
DOI: 10.1371/journal.pone.0158890
|View full text |Cite
|
Sign up to set email alerts
|

CYP2B6rs2279343 Is Associated with Improved Survival of Pediatric Rhabdomyosarcoma Treated with Cyclophosphamide

Abstract: BackgroundRhabdomyosarcoma (RMS) is a small round blue cell malignant tumor, representing 7% of childhood malignancies, and over 50% of all soft tissue sarcomas. Cyclophosphamide (CPA) is a prodrug and is the mainstay of RMS treatment. CYP2B6 is a highly polymorphic drug metabolizing enzyme involved in CPA bioactivation. The influence of CYP2B6 single nucleotide polymorphisms (SNPs) on the survival of RMS is still unknown.MethodsWe genotyped CYP2B6SNPs rs2279343, rs3745274, and rs3211371 by restriction fragmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…The allelic frequencies of Q172H and K262R were 11% and 33% respectively. Earlier studies found similar frequencies both for K262R and Q172H [4,[12][13][14]. Allelic frequencies of the investigated GST genes were quite diverse, both variant and wild type alleles were abundant in all three cases ( Table 2).…”
Section: Allele Frequenciessupporting
confidence: 56%
“…The allelic frequencies of Q172H and K262R were 11% and 33% respectively. Earlier studies found similar frequencies both for K262R and Q172H [4,[12][13][14]. Allelic frequencies of the investigated GST genes were quite diverse, both variant and wild type alleles were abundant in all three cases ( Table 2).…”
Section: Allele Frequenciessupporting
confidence: 56%
“…The effect of genetic polymorphisms on CYC’s efficacy when it is used in combination with other chemotherapeutic agents was studied in another 2 studies and the results were CYP2B6 GT and TT are related to diminished effect to CYC and fludarabine in individuals with Leukemia, Lymphocytic, Persistent, B-Cell when contrasted with CYP2B6 GG [33]. The other study [34] concluded that the increased overall survival was not related to genotypes GT and TT after treatment with CYC, dactinomycin, and vincristine in children compared with genotype GG. Table 4 summarizes all tolerability/ toxicity-related parameters, about 44.5% of GG genotype patients developed multiple infections versus 42 and 13.5% in GT and TT genotype patients respectively and there was not any statistically significant difference between the different genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…The low hepatic expressions of c.516G>T and c.785A>G SNPs observed in BUP reflected variable activities. Meanwhile, SNPs at positions 516 and 785 on the CYP2B6 gene are essential in the metabolism of several drugs [ 33 , 34 ]. CYP2B6 T516T was definitely related to plasma concentration, supporting its effect on lower pharmacokinetic parameters of BUP [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although high plasma BUP levels were observed in CYP2B6*9 participants at all time-points, they were all well-tolerated within the therapeutic window and had no adverse effects. The functional impacts of CYP2B6 A785G are associated with the enhanced catalytic activation of hydroxylation [ 34 ], exhibiting rapidly metabolic activity. CYP2B6 catalyzed the hydroxylation of a diverse number of xenobiotics, and the metabolic activity in hydroxylation relied on SNPs [ 35 ].…”
Section: Discussionmentioning
confidence: 99%